1994
DOI: 10.1159/000154211
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Delta-Aminolevulinate Dehydratase in the Upper Silesian Population, Poland

Abstract: The δ-aminolevulinate dehydratase (ALADH) polymorphism was studied in the Upper Silesian population, Poland. The frequency of ALADH*1 was 0.9417, and ALADH*2 was 0.0583. No rare or anomalous phenotype was found. The distribution of phenotypes in 148 mother-child pairs was determined. Comparison with other world populations was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…This finding is similar with most European populations in that ALAD1 frequency ranges from 0.84 to 0.94 [Petrucci et al, 1982; Benkmann et al, 1983;Amorim et al, 1994, Raczek, 1994. In comparison, Asian populations have low ALAD2 allele frequencies [Zhang et al, 1998;Hsieh et al, 2000;Sakai et al, 2000b] and Petrucci et al [1982] found none in an African population.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is similar with most European populations in that ALAD1 frequency ranges from 0.84 to 0.94 [Petrucci et al, 1982; Benkmann et al, 1983;Amorim et al, 1994, Raczek, 1994. In comparison, Asian populations have low ALAD2 allele frequencies [Zhang et al, 1998;Hsieh et al, 2000;Sakai et al, 2000b] and Petrucci et al [1982] found none in an African population.…”
Section: Discussionsupporting
confidence: 84%
“…ALAD polymorphism has been demonstrated to vary with racial group. The frequency of ALAD2 allele is found in about 10% of the Caucasian population (8,17,18), 3–4% of Chinese Han population (19,20), but is was not detected in an African population (21). This study found that the proportion among Uygur population with ALAD1‐1/1‐2 genotype and ALAD2 allele was higher than among the Han population.…”
Section: Discussionmentioning
confidence: 99%